Analisis Pengaruh Good Corporate Governance (GCG) Terhadap Profil Risiko Dan Rentabilitas Bank Umum Di Indonesia Tahun 2011-2015 - Widiamsa, Abraham William (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
ABSTRACT. The purpose of this research is to analyze the influence of good corporate governace (GCG) of profile risks and rentabilitas commercial banks in Indonesia on 2011-2015. Good governance coporate (GCG) measured by the composite self assessment commercial banks. Profile risk commercial banks measured by non performing loan (NPL), the net open position (NOP) and loan to deposit the ratio (LDR). Rentabilitas commercial banks measured by return on assets (ROA) and net interest margin (NIM). The research results show that GCG have a negative influence on NPL. GCG has not been affecting the PDN and LDR. GCG influential positive to ROA and NIM. This research using sample 23 commercial banks in indonesia listed on the Indonesian Stock Exchange (IDX).Keywords: self assessment good corporate governance the composite, NPL, NOP, LDR, ROA, NIM, commercial banks